Understanding the spatial and topographic characteristics of enamel white spot lesions for targeted remineralization - Devanshi Rajesh Chhabria; Ramya Ramadoss, MDS.,PhD; Hema Shree K, MDS; Sandhya Sundar, MDS; Suganya Panneer Selvam, MDS; Pratibha Ramani, MDS.,PhD (Elsevier, 2024)
Introduction: White spot lesions are opaque, chalky white or yellowish discolorations on the surface of teeth that result from the demineralization of the tooth structure. Many methods, including SEM, XRD, and FTIR spectroscopy, are crucial for identifying and evaluating enamel white spot lesions. It is imperative to have a thorough grasp of the morphology, crystallographic structure, mineral composition, and chemical changes associated with enamel white spot lesions. Method: In vitro lesions were meticulously obtained by immersing extracted teeth in hydrochloric acid for a week and drying them using artificial caries. Characterization investigations were conducted with utmost precision and thoroughness using FTIR, XRD, and SEM, ensuring the reliability and validity of the results. Results: FTIR analysis revealed the existence of calcium oxide and hydroxyapatite, and SEM examination assisted in identifying differences in surface shape. The enamel's crystalline nature was revealed via XRD investigation. Conclusion: White spot lesions are associated with the development of deep caries. Advanced imaging strategies are needed for additional validation.